Profit Sharing Mechanism of Large EPC Project considering the Behavior of Fairness Concern - Huimin Li; Lelin Lv; Xiaowei An; Guanghua Dong (Advances in Civil Engineering)
A large-scale engineering procurement and construction (EPC) project is often conducted by a joint venture. Many factors affect the success of cooperation among participating enterprises, such as trust and the degree of effort of both parties. The most important one is a rational profit sharing mechanism. Reasonable profit sharing mechanism concerns whether the advantages of the EPC model can be fully utilized. In this study, the proposed EPC project is undertaken by a joint venture integrating design and construction enterprises. Moreover, the profit sharing problem arises from the project optimization implemented by both parties. The fairness concern behavior of both parties is considered, and the profit sharing model for the EPC project is established on the basis of game theory. The effect of the fairness concern behavior of both parties on the EPC project optimization and its profit sharing is further analyzed by simulation analysis. The research findings show that the project optimization profit and its sharing are related to not only the efforts and cost coefficient but also the fairness concern behavior of both parties. The research results are conducive to the application of the EPC model in the field of construction engineering.